Contact patterning by laser printing for flexible electronics on paper - Angela F. Harper (Nature Portfolio, 2019)
Desktop printers and sprayers powering flexible electronics The power of commercial printers and spray coaters has been brought together to fasten the prototyping of flexible electronics. A collaborative team led by Prof Oana Jurchescu from Wake Forest University, US design an aerosol spray laser lithography approach to make patterned electrode arrays with low cost. The lithography step is realized by a desktop laser printer while the toner acts as the photoresist. The electrodes are deposited with spray coating of metal inks, followed by a heat-assisted transfer or peel-off process to finish the patterning. They then printed organic thin-film transistor arrays on paper and show that the devices work well under normal and bending conditions. This approach has proven successful, easy and compatible in fabricating flexible transistor arrays. It can be expected to fasten the pace in prototyping and manufacturing of flexible electronics.